A novel method for the design of diffractive optical elements based on the Rayleigh–Sommerfeld integral. (July 2015) - Pang, Hui; Yin, Shaoyun; Deng, Qiling; Qiu, Qi; Du, Chunlei
Abstract: The original design method for diffractive optical elements (DOEs) is limited to cases of small-angle diffraction due to the Fresnel or Fraunhofer diffraction integral. In this paper, we propose a new method based on the Rayleigh–Sommerfeld diffraction integral, which does not have this limit. In this method, the target intensity distribution is first modified via coordinate transformation and intensity adjustment. Then, the modified Gerchberg–Saxton algorithm is used to achieve the phase distribution of the DOE. To verify this method, simulations and experiments are performed. The results show that the original method is effective only when the full diffraction angle of the DOE is below 25°. Conversely, this method can achieve the target with both small and large diffraction angles. Highlights: We propose a new method for design the DOE with Rayleigh–Sommerfeld integral. The original method is effective only when the diffraction angle of DOE is below 25°. In contrast, our method is effective in both the case of small and large diffraction angle.